SECURITY FROM THE PERSPECTIVES OF REALISM, COPENHAGEN, LIBERALISM WITH A LITTLE TASTE OF TECHNOLOGY - Seyed Mohammad Ardam, Ellias Aghili Dehnavi, Mohammad Ghanbari Barzyan, Amir Parvaresh (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Security is one of the concepts in the humanities that, like many other concepts (society, culture, value ...). Complexity and ambiguity are its inherent characteristics. Security is the main task of the national government and the most important issue. It has so far been considered by scholars under such topics as war and peace, strategic studies and national security studies International relations. Therefore, in this study, we use the descriptive-analytical method in Perry We are the answer to the fundamental question of how the schools of realism, Copenhagen and liberalism view security. Hypothesis Research shows that realism sees security in survival and a social contract, Copenhagen believes Security is made by the minds and decisions of the actors, and liberalism believes in security in free ideas and the profit-oriented nature of man LT is. In this study, we first address the concept of security and then examine the schools of realism, Copenhagen and we look at liberalism and look at security from their perspective; we also have conducted a brief study regarding the relation between security and technology.